The determinants of stock market return (KLCI) in Malaysia / Nor Hidayah Mazlan - Mazlan, Nor Hidayah (Faculty of Business and Management, 2015)
This paper aims is finding out the effect of macroeconomic determinant on stock market performance in Malaysia. The study is focuses on stock index which is FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBMKLCI). The macroeconomic variables considered are interest rate (3 month interbank rates), exchange rate, crude palm oil price, money supply (M2) and inflation rate. The sample of this study comprises of 60 observations each of the independent and dependent variables on a monthly basis over 5 years period from January 2010 to December 2014. In order to calculate the stock market return, there are two approaches being used which are Capital Asset Pricing Model (CAPM) and also Arbitrage Pricing Theory (APT). Both of the approaches being used to determine the stock market return by relate it with the macroeconomic factors that affect its return. It is essential to determine whether the microeconomic variables has positive or negative relationship with the stock market return in order to give the knowledge to the public like what will happen when there are uncertainty in investment. Methodology used for this study is by using Multiple Linear Regression with time series data sourced from DataStream. Thereafter, econometric tests are to be conducted to observe the relationship of the macroeconomic variables to the FBMKLCI. Interactive software package Eview 7 would be used for testing and analyzing the data collected. The study is an attempt to investigate the relationship of the chosen macroeconomic variables towards influencing stock index which is FBMKLCI. Findings from previous research papers mostly on developed markets indicate that macroeconomic variables do play a significant role in the determination of stock returns. The results of this research paper would provide an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.